Brain death in cultural context – an outline of the issue - Wójcik, Bogusław (Health Promotion & Physical Activity, 2018)
Half a century after the introduction criteria of brain death by the Harvard Ad HocCommitteeonBrainDeath, the discussions on their methodological consistency, biological adequacy and medical legitimacy do not cease. On the one hand, the appearance of these criteria solved, some of the ethical dilemmas caused by medical advances and technological progress, with the other hand, common beliefs about the phenomenon of death have no changed. For these reasons growing in importance opinions indicating a need to revise the guidelines, which enabled the introduction of these criteria, or return to the previous status quo. In this article I justified that uncritical acceptance, that every scientific concept can be defined only in terms of a set of empirical operations would be manifestation of naive realism.But it would be equally naive to reject beliefs, that death is a biological fact, that can be studied, described and modeled according to modern scientific standards.